Selected legal issues in Islamic family law, waqf, inheritance, halal and Islamic finance: extended abstracts & compilation of slides - Mohamad, Nor Asiah (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), IIUM, 2025)
This book contains a compilation of extended abstract and slides from a Conference and A Round Table Discussion